2010
DOI: 10.1007/s00392-010-0216-9
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive servoventilation improves cardiac function and respiratory stability

Abstract: Cheyne–Stokes respiration (CSR) in patients with chronic heart failure (CHF) is of major prognostic impact and expresses respiratory instability. Other parameters are daytime pCO2, VE/VCO2-slope during exercise, exertional oscillatory ventilation (EOV), and increased sensitivity of central CO2 receptors. Adaptive servoventilation (ASV) was introduced to specifically treat CSR in CHF. Aim of this study was to investigate ASV effects on CSR, cardiac function, and respiratory stability. A total of 105 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 36 publications
3
55
2
1
Order By: Relevance
“…4 Values are mean ± standard deviation. Group A = moderate-to-severe SDB (AHI > -20), ASV-treated patients; Group B = moderate-to-severe SDB (AHI > -20), non-ASV-treated patients; Group C = non-to-mild SDB (AHI <20), ASV-treated patients; Group D = non-to-mild SDB (AHI <20), non-ASV-treated patients.…”
Section: Asv and Prognosis Of Hfmentioning
confidence: 99%
“…4 Values are mean ± standard deviation. Group A = moderate-to-severe SDB (AHI > -20), ASV-treated patients; Group B = moderate-to-severe SDB (AHI > -20), non-ASV-treated patients; Group C = non-to-mild SDB (AHI <20), ASV-treated patients; Group D = non-to-mild SDB (AHI <20), non-ASV-treated patients.…”
Section: Asv and Prognosis Of Hfmentioning
confidence: 99%
“…Thus, the final result might be more stable respiration with improved respiratory control. 30 OSA and CSA-CSR, in particular, are associated with increased sympathetic drive, 66 which is independently associated with poor prognosis in HF. 67, 68 In combination with other contributing factors such as oxygen desaturation, increased LV wall tension and afterload, and BP changes, this may lead to malignant ventricular arrhythmias, which have been documented in these patients.…”
Section: Long-term Effects Of Asv In Hf Patientsmentioning
confidence: 99%
“…28 Most HF patients with nocturnal CSA-CSR hyperventilate even while awake during the daytime. 8,29, 30 This hyperventilation may be a result of stimulation of pulmonary vagal irritant receptors by pulmonary congestion in combination with enhanced central and peripheral chemoreceptor sensitivity and prolonged circulation time. 31,32 In HF patients with CSA-CSR, carbon dioxide (CO2)-dependent apnea thresholds are altered, 33 making them more sensitive to apnea with decreasing CO2 partial pressure (pCO2).…”
Section: Pathophysiology Of Csrmentioning
confidence: 99%
See 1 more Smart Citation
“…Left VentricuLar ejection fraction: Nineteen studies 5,[7][8][9][10][11][12][13][14][15]18,19,[22][23][24]27,29,32 reported on the effects of ASV on LVEF. The meta-analysis of the change in LVEF with treatment versus baseline is shown in Figure S1 in the supplemental material.…”
Section: -32mentioning
confidence: 99%